59.5k views
1 vote
Solve for x 2x^2 + x - 1 = 2

User SimonJ
by
5.8k points

2 Answers

5 votes

Answer:

x= -3/2 or 1

Explanation:

2x^2 +x-1=2

2x^2 +x-3=0

(2x+3)(x-1)=0

2x+3=0 x-1=0

2x= -3 x=1

x= -3/2 x=1

User Dodi
by
6.3k points
5 votes

Answer:

x = -
(3)/(2), x = 1

Explanation:

Given

2x² + x - 1 = 2 ( subtract 2 from both sides )

2x² + x - 3 = 0 ← in standard form

(2x + 3)(x - 1) = 0 ← in factored form

Equate each factor to zero and solve for x

2x + 3 = 0 ⇒ 2x = - 3 ⇒ x = -
(3)/(2)

x - 1 = 0 ⇒ x = 1

User Doug Smith
by
6.1k points